Adiabatic burst evaporation from bicontinuous nanoporous membranes. Issue 20 (28th May 2015) - Ichilmann, Sachar; Rücker, Kerstin; Haase, Markus; Enke, Dirk; Steinhart, Martin; Xue, Longjian
<x xml:space="preserve">Abstract</x> We show that besides endothermic evaporation avalanche-like adiabatic burst evaporation significantly contributes to evaporation from bicontinuous nanoporous media.